Psycholegal Research: Past and Present - Loh, Wallace D. (1981)
A Review of The Psychology of Eyewitness Testimony by A. Daniel Yarmey, and Eyewitness Testimony by Elizabeth F. Loftus, and Social Psychology in Court by Michael J. Saks and Reid Hastie, and The Criminal Justice System and Its Psychology by Alfred Cohn and Roy Udol